2013
DOI: 10.1007/s11250-013-0454-8
|View full text |Cite
|
Sign up to set email alerts
|

Udder health in relation to udder and teat morphometry in Holstein Friesian × Sahiwal crossbred dairy cows

Abstract: The present investigation involved 261 Holstein Friesian (HF) × Sahiwal cows to study the udder health as well as the udder and teat morphometry. The udder health was defined on the basis of bacteriology and California mastitis test of quarter foremilk. The morphometry parameters included udder fore depth (UFD, distance from the point where the fore udder merges within the abdomen to a point in front of the fore teats at the level of the udder base), udder rear depth (URD, distance from the bottom of the vulva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 15 publications
8
14
1
Order By: Relevance
“…In any case, there is no consensus in the literature about the influence of teat morphology on mastitis occurrence [14,16]. In the present investigation, phagocytic activity of milk neutrophils was negatively correlated with teat length, whereas Con A induced in vitro milk lymphocyte blastogenic response and PI of milk macrophages were negatively correlated.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…In any case, there is no consensus in the literature about the influence of teat morphology on mastitis occurrence [14,16]. In the present investigation, phagocytic activity of milk neutrophils was negatively correlated with teat length, whereas Con A induced in vitro milk lymphocyte blastogenic response and PI of milk macrophages were negatively correlated.…”
Section: Discussioncontrasting
confidence: 40%
“…[6] and Singh et al . [14] also reported decreasing teat end to floor distance, is a well-documented risk factor for mastitis.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies had also reported a significant effect of udder morphology and stated that cows with pendulous udders had the highest risk of mastitis [12] and higher SCC [13]. Our results are also supported by other studies, where the deeper udders were found to be at higher risk of developing mastitis due to their increased tendency to become soiled [14] and more susceptible to lesions [6][7], hence, being contaminated with environmental pathogens and developed mastitis. However, some study [15] found the insignificant effect of udder shape on SCC and a significant negative correlation between somatic cell number and udder depth has been also reported by Orban et al [16].…”
Section: Udder Shape and Sccsupporting
confidence: 89%
“…No evidence for this has yet been found for dairy buffaloes. Previously, a smaller teat-end to floor distance was shown to be associated with increased risk of SCC or IMI in dairy cows (Porcionato et al 2010;Singh et al 2014).…”
Section: Teat Morphometry and Quarter Healthmentioning
confidence: 99%